2021
DOI: 10.3389/fonc.2021.637247
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-125b Exerts Anti-Metastatic Properties and Predicts Early Metastasis of Hepatocellular Carcinoma

Abstract: Background & AimsCancer metastasis is responsible for the majority of cancer-related deaths. Exosomal miRNAs have emerged as promising biomarkers for cancer, serving as signaling molecules that can regulate tumor growth and metastasis. This study examined circulating exosomal miRNAs that could predict hepatocellular carcinoma (HCC) metastasis.MethodsExosomal miRNA was measured by quantitative real-time PCR (qRT-PCR) in a large set of patients (n = 284). To investigate the role of exosomal miRNA in HCC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Hisakane et al 84 revealed that miR-210-3p was upregulated in exosomes isolated from osimertinib-resistant HCC827, and their study found that exosomal miR-210-3p may promote EMT and induce resistance to osimertinib in HCC827 cells (a type of lung cancer cell line). Conversely, Kim et al 85 revealed that exosome-mediated miR-125b transfer disrupted TGF-β1-induced EMT and TGF-β1/SMAD signaling pathway in recipient cells via decreasing SMAD2 protein expression. In addition, exosomal miR-125b expression was downregulated after metastasis.…”
Section: Exosomes Regulate Tme In the Drug Resistance Of Hccmentioning
confidence: 98%
See 1 more Smart Citation
“…Hisakane et al 84 revealed that miR-210-3p was upregulated in exosomes isolated from osimertinib-resistant HCC827, and their study found that exosomal miR-210-3p may promote EMT and induce resistance to osimertinib in HCC827 cells (a type of lung cancer cell line). Conversely, Kim et al 85 revealed that exosome-mediated miR-125b transfer disrupted TGF-β1-induced EMT and TGF-β1/SMAD signaling pathway in recipient cells via decreasing SMAD2 protein expression. In addition, exosomal miR-125b expression was downregulated after metastasis.…”
Section: Exosomes Regulate Tme In the Drug Resistance Of Hccmentioning
confidence: 98%
“… 24 Theoretically, these studies provide more accurate information for predicting the treatment response of HCC. Kim et al 85 believed that exosomal miR-125b may be a reliable biomarker for the diagnosis and evaluation of extrahepatic metastasis of HCC. Zhu et al 91 established a prognosis and recurrence risk prediction model, which presented a significant predictive performance, based on two exosomal genes (MYL6B and THOC2).…”
Section: Potential Clinical Applications Of Exosomes In Hcc Drug Resi...mentioning
confidence: 99%
“…Exosomal miR-125b exerts an anti-metastatic effect through interfering TGF-β1-induced epithelial-mesenchymal transition (EMT) and therefore drastically downregulated miR-125b predicts early metastasis of HCC (Kim et al, 2021). Circulating exosomal miR-1307-5p promotes metastasis and helps predict metastasis in HCC through targeting the tumor suppressor genes SEC14L2 and ENG to promote EMT (Eun et al, 2020).…”
Section: Exosomes In Hcc Diagnosis and Prognosismentioning
confidence: 99%
“…Interestingly, the plasma exosomal miRNAs could also serve as potential metastasis-related biomarkers for HCC ( Huang et al, 2021 ; Kim et al, 2021 ). Huang et al ( Huang et al, 2021 ) showed a total of 32 differentially expressed miRNAs in the plasma exosomes of patients with metastatic HCC compared with those without metastasis and the combination of three miRNAs (miR-18a, miR-27a and miR-20b) could discriminate metastatic HCC from non-metastatic HCC.…”
Section: Exosomes In Hcc Diagnosis and Prognosismentioning
confidence: 99%
“…Apart from their early diagnostic value, sEV cargos may be involved in the prediction of tumor staging and metastasis (144)(145)(146)(147). Exo-miR-1307-5p expression in plasma has been found to be positively associated with tumor stage and progression, while sEVs carrying miR-125b have been shown to possess anti-metastatic features and are indicators of early metastasis in HCC (148)(149)(150). Other sEV cargos can play a similar role in tumor staging or metastasis prediction, and the function of lncRNA ATB, hnRNPH1 and ASMTL-AS1 in this regard has been reported (151)(152)(153).…”
Section: Clinical Applications Of Sevs In Hcc Sevs As Diagnostic and ...mentioning
confidence: 99%